Utilization Of Voice Of Customer From Online Patient Reviews On Google Maps As A Source Of Business Intelligence In The Evaluation Of Rata.Id Clinic Services In 2025 - Galuh Nurvinda Kurniawati; Andi Wijayanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines the use of Voice of Customer data from online patient reviews on Google Maps as a source of business intelligence for evaluating the service quality of Rata.id Clinics. Using a Natural Language Processing (NLP)-based text analytics approach, this study applied sentiment analysis, bigram-based thematic analysis, and SERVQUAL mapping to analyze 390 patient reviews collected from 3 Rata.id Clinic branches. The results showed that the quality of services had been generally rated positively by the patients, especially at the Branch of Bandung. The relatively high negative sentiment at the Rata Clinic Center (RCC) and Gading Serpong branches, however, indicates disparities in the quality of service provided at the branches. The results of SERVQUAL mapping provides that all the clinic branches possess the following strengths: empathy, tangibles, and the main area for improvement is responsiveness. The main concerns that were identified are response time, service communication, lack of clarity regarding costs and service consistency. The results show that customer insights and business intelligence can be gained from patient online reviews, which are useful for the assessment and enhancement of healthcare services.